IN SILICO INVESTIGATION OF ANTIFUNGAL BIOACTIVE COMPOUNDS FROM Areca catechu SEEDS: INVESTIGASI IN SILICO SENYAWA BIOAKTIF ANTIJAMUR DARI BIJI PINANG (Areca catechu) - Erwan; Egi Saputra; Deky Alfiansyah; Muhammad Farell Islami Pasha; Julianti; Iqlima Nadya Putri; Dodi Iskandar; Dimas Fitra Miardhan (ROCE : Jurnal Pertanian Terapan, 2026)
This study evaluated the antifungal potential of bioactive compounds present in betel nut seeds (Areca catechu L.) through an in silico approach. The assessment included prediction of antifungal activity (Pa), pharmacokinetic profiling using SwissADME, evaluation of physicochemical and drug-likeness properties, and toxicity prediction with pkCSM. The results indicated that betel nut seeds contain various bioactive constituents, including phenolic compounds, flavonoids, alkaloids, fatty acids, and proanthocyanidins, which may contribute to antifungal activity through different mechanisms. Among the analyzed compounds, proanthocyanidins showed the highest predicted antifungal activity, followed by arecoline and catechin. These compounds are expected to inhibit fungal growth by disrupting cell membrane integrity, reducing biofilm formation, and interfering with essential metabolic pathways. Pharmacokinetic analysis revealed that low-molecular-weight compounds, such as catechin, certain alkaloids, and fatty acids, generally exhibited greater solubility and drug-likeness, suggesting greater bioavailability. In contrast, larger polyphenolic compounds demonstrated lower absorption potential but may remain active through direct interactions with fungal cell surfaces. Toxicity predictions suggested that most compounds pose relatively low mutagenic risk, although some alkaloids may have hepatotoxic potential. Overall, the findings indicate that the antifungal properties of Areca catechu are likely attributable to the combined action of multiple bioactive compounds, highlighting its potential as a natural source for developing environmentally friendly antifungal agents.